PENGEMBANGAN MODEL PENANGANAN TINDAKAN BULLYING PADA SISWA SMA/SMK DI KOTA YOGYAKARTA - Siti Hafsah Budi Argiyati (JURNAL SPIRITS, 2012)
ABSTRACTThis research is aimed to produce a treatment method for bullying in high schools/vocational schools in the city of Yogyakarta. More specifically, the research is expected to (1) describe the intensity of bullying among students, (2) identify problems that occur in the field, (3) describe the perceptions of teachers, students, and parents on the implementation of the handling of bullying.The study was conducted at six senior high schools/vocational schools in the city of Yogyakarta as a whole, amounted to 353 students, 115 school staffs and 47 parents of students. Data obtained using the documentation, the scale, in-depth interviews, and observation technique. The scale is designed to identify the victims and perpetrators of bullying and the perception of teachers, learners, and parents to acts of bullying in schools. Observation technique is used to examine the teaching and learning process. While interview is used to dig deeper understanding in matters related to the handling of bullying. The study will conclude by outlining a treatment model whereby to meet the challenge of school bullying.Key words: model, bullying, senior high school / vocational school